Chiral separation of calcium channel antagonists by SFC and HPLC using different immobilized chiral stationary phases. Issue 3 (5th January 2022) - Raja, Rupak; Alam, Syed Dilshad; Mukhopadhyay, Dipanjan; Shirsath, Vikas; Jain, Arvind K.; ALOthman, Zeid A.; Locatelli, Marcello; Ali, Imran
Abstract: Supercritical fluid chromatography and high‐performance liquid chromatography techniques are popular for the chiral separations of different drugs and pharmaceuticals. Therefore, this article describes a comparative study of the chiral separation of some calcium channel antagonists such as verapamil, gallopamil, and nisoldipine. The columns used were Chiralpak IG and Chiralpak ID (250 mm × 4.6 mm, 5.0 μm). The separation was achieved by using a variety of mobile phases in both techniques. The retention, separation, and resolution factors in SFC were in the range of 1.36–7.30, 1.09–1.72, and 1.16–3.47, while these values in the case of HPLC were 1.03–2.42, 1.12–1.35, and 0.49–2.46. The complete resolution of gallopamil and verapamil was achieved successfully. The chiral recognition was controlled by hydrogen bondings, π‐π interactions, dipole induced dipole interactions, van der Waal forces, and steric effects. SFC was found to be a better technique than HPLC because of quick separation, good separation power, economic, environment‐friendly, and green technology. Abstract :